Heterostructured Copper-Ceria and Iron-Ceria Nanorods Role of Morphology, Redox, and Acid Properties in Catalytic Diesel Soot Combustion - Sudarsanam, Putla (Langmuir : the ACS journal of surfaces and colloids, 2018)
This work reports the synthesis of heterostructured copper-ceria and iron-ceria nanorods and the role of their morphology, redox, and acid properties in catalytic diesel soot combustion. Microscopy images show the presence of nanocrystalline CuO (9.5 ± 0.5 nm) and Fe2O3 (7.3 ± 0.5 nm) particles on the surface of CeO2 nanorods (diameter is 8.5 ± 2 nm and length within 16-89 nm). In addition to diffraction peaks of CuO and Fe2O3 nanocrystallites, X-ray diffraction (XRD) studies reveal doping of Cu2+ and Fe3+ ions into the fluorite lattice of CeO2, hence abundant oxygen vacancies in the Cu/CeO2 and Fe/CeO2 nanorods, as evidenced by Raman spectroscopy studies. XRD and Raman spectroscopy studies further show substantial perturbations in Cu/CeO2 rods, resulting in an improved reducibility of bulk cerium oxide and formation of abundant Lewis acid sites, as investigated by H2-temperature-programmed reduction and pyridine-adsorbed Fourier transform infrared studies, respectively. The Cu/CeO2 rods catalyze the soot oxidation reaction at the lowest temperatures under both tight contact (Cu/CeO2; T50 = 358 °C, temperature at which 50% soot conversion is achieved, followed by Fe/CeO2; T50 = 368 °C and CeO2; T50 = 433 °C) and loose contact conditions (Cu/CeO2; T50 = 419 °C and Fe/CeO2; T50 = 435 °C). A possible mechanism based on the synergetic effect of redox and acid properties of Cu/CeO2 nanorods was proposed: acid sites can activate soot particles to form reactive carbon species, which are oxidized by gaseous oxygen/lattice oxygen activated in the oxygen vacancies (redox sites) of ceria rods